Odpowiedź :
Odpowiedź:
a)
[tex]x_{1,\:2}=\frac{-3\pm \sqrt{3^2-4\cdot \:1\cdot \left(-40\right)}}{2\cdot \:1}\\x=5,\:x=-8[/tex]
postać iloczynowa:
[tex]f(x)=x^2+3x-40=\left(x-5\right)\left(x+8\right)[/tex]
b)
[tex]x_{1,\:2}=\frac{-5\pm \sqrt{5^2-4\left(-2\right)\left(-2\right)}}{2\left(-2\right)}\\x=\frac{1}{2},\:x=2[/tex]
postać iloczynowa:
[tex]-2x^2+5x-2=-\left(2x-1\right)\left(x-2\right)[/tex]
c)
[tex]2\left(x-1\right)^2-50=0 \\2\left(x-1\right)^2=50\\(x-1)^2=25\\\boxed{x-1=5 }\;\;\; \text{lub } \boxed{x-1=-5}\\x=6,\:x=-4[/tex]
postać iloczynowa:
[tex]2\left(x-1\right)^2-50=2\left(x+4\right)\left(x-6\right)[/tex]